PENGARUH CASH RATIO, RETURN ON ASSET DAN GROWTH TERHADAP DIVIDEN PAYOUT RATIO PERUSAHAAN INDUSTRI PERTAMBANGAN DI BURSA EFEK INDONESIA TAHUN 2008-2010 - SANTI YULIA NIRVA SARI (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
The study was conducted to examine the effect of variable cash ratio, Retun On Assets (ROA), and the Growth Dividend Payout Ratio against the mining company listed on the Indonesia Stock Exchange in the period 2008-2010. The population in this study some 11 mining companies listed on the Indonesia Stock Exchange in the period 2008-2010. Sampling technique used was purposive sampling criteria: (1) The mining companies that provide financial statements in the period 2008-2010, based on the recapitulation of the company's performance as published by the Indonesia Stock Exchange through www.idx.co.id. (2) The mining company that is continuously distributed dividends in the period 2008-2010, based on the payout ratio as published by the Indonesia Stock Exchange through www.idx.co.id. (3) The mining company that produces profitability in the period 2008-2010, based on the recapitulation of the company's performance as published by the Indonesia Stock Exchange through www.idx.co.id. Data obtained from the publication of the Indonesia Stock Exchange 2008-2010. Obtained the sample of 11 companies. Analysis technique used is multiple regression by the least squares equations and hypothesis testing using the t-statistic for testing the partial regression coefficients and F-statistics to test the effect together with the confidence level of 5%. The results showed that the Cash Ratio (CR) significantly influence the House of Representatives. While the Return On Asset (ROA) and Growth no significant effect on the House. We suggest to investors in Indonesia Stock Exchange in order to give more attention to information released by the company in making their investment decisions. Variable Cash Ratio in this study is the most influential variable on the House indicated the significance of the value of 0.028, Return On Asset (ROA) to the value of significance is 0.169, and Growth with a significance value is 0.841.